Kota Sehat sebagai Bentuk Sustainable Communities Best Practice - Soedirham, Oedojo (UI Scholars Hub, 2012)
Kota Sehat merupakan proyek World Health Organization (WHO) yang diluncurkan pada pertengahan tahun 1980-an dengan mengambil tempat untuk yang pertama kali adalah kota-kota di Eropa. Konsep Kota Sehat adalah konsep lama sekaligus baru. “Lama” berarti telah lama manusia berusaha untuk membuat kota lebih sehat sejak awal peradaban perkotaan (urban civilization). “Baru” dalam manifestasinya sebagai satu sarana utama promosi kesehatan – kesehatan masyarakat baru (new public health) – dalam pencarian Sehat untuk Semua (Health for All). Hal tersebut dipandang sebagai “a means of legitimizing, nurturing, and supporting the process of community empowerment”. Artikel ini mengulas Kota Sehat dalam konteks sustainable communities. Healthy City is a World Health Organization (WHO) project that launched in mid 1980s with cities at Europe as first attempts. The Healthy City concept is old and new. “Old” means that since the early urban civilization, humanbeing striving for better and healthier places to live. “New” means that it’s one primary manifestation for health promotion – new public health – in seeking “Health for All”. This is seen as “a means of legitimizing, nurturing, and supporting the process of community empowerment”. The paper reviewed Healthy City in sustainable communities context.